STRATEGI MENINGKATKAN MOTIVASI KERJA KARYAWAN STUDY KASUS DI HAUS KETINTANG - Muhamad Angga Sangkara; Ahmad Septiyan Saputra; Agus Wahyudi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Strategies to increase employee motivation at Haus Ketintang, an F&B company that operates as a franchise and has a dynamic and competitive business background. This research aims to identify internal and external factors that influence employee motivation and performance and formulate effective strategies to encourage work enthusiasm and productivity. The methodology used is qualitative research with a Grounded Theory approach, which is supported by documentation studies from various literature sources and field experiences. The results show that a positive work environment, recognition, soft skill and hard skill development training, as well as motivation through rewards and career development opportunities can significantly improve employee motivation and performance. This paper emphasizes the importance of the role of managerial strategies in creating a conducive work atmosphere to support the company's success in achieving its business goals.